Pelaksanaan Peradilan Elektronik (E-Court) Dalam Penyelesaian Perkara Di Pengadilan Tata Usaha Negara Mataram - MAKSUM, HAIRUL (Fakultas Hukum Universitas Gunung Rinjani, 2024)
This study aims to know, analyze, and provide an understanding of the implementation of e-court and the challenges and obstacles in the implementation of e-court at the Mataram State Administrative Court.This research uses empirical normative research methods using approach methods, namely the statutory approach (statute approach), conceptual approach (conceptual approach), sociological approach (sociological approach), and historical approach (historical approach). Electronic trials (e-litigation) can be conducted when the user gets an electronic call (e-summon). In this electronic trial, there must be approval from the opposing party, when the opposing party agrees, the trial will be held electronically, however, if there is no agreement from the opposing party, there is no electronic trial. The formulation of the problem in this study is How is the implementation of PERMA NO. 1 of 2019 concerning Electronic Administration of Cases and Trials in Court?; How is the Implementation of E-court on Case Settlement at the Mataram State Administrative Court?; and What are the Challenges and Obstacles During Litigation Using E-court at the Mataram State Administrative Court? With this E-court, the judiciary becomes more transparent and accountable in resolving cases